Michael Klein on the Targums : collected essays 1972-2002 - Klein, Michael L. (Studies in the Aramaic interpretation of Scripture ;, 2011)
During his life, Michael Klein played a key role in helping establish the foundation for the modern study of the Targums. He was known for his thorough studies of targumic translation techniques and for his editions of the Fragment Targums and the Cairo Geniza fragments of Palestinian Targums. This collection of his essays brings together some of his writings on translation technique and studies on the Cairo Geniza material on Targums Onqelos and Jonathan, as well as the Writings. Essays on the Palestinian Targums feature as well, with studies of Targum Neofiti and Geniza discoveries that occu.